Slovenske ljudske pravljice na višji stopnji slovenske osnovne šole Slovenian Folktales at the Upper Level of Slovenian Primary Schools - Novak, Petra (Studia mythologica Slavica, 2013)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This article presents, with the help of comparative analysis, fairy tales included into Slovenian curriculum and textbooks of various publishers for upper level of primary school. The main part of the discussion represents all the texts with fairy-tale elements that are included in the analysed literary learning books from the genre and motif point of view. Each interpretation of the text includes didactic and literary instruments that present fairy tale elements to pupils.